L'Art à l'Hôpital en Europe : Brussel - Madrid - Paris. - Arrojo de Lamo, Fran; Bailly, Virginie; Baztán Lacasa, Carlos; Claeyé, Catherine; Even, Rachel; Faucher, Michel; Fernagu, Harald; Rebeyrat, Sandrine (Sceaux : Art dans la Cité, 2001)
The Art in European Hospitals Brussels, Madrid, Paris exhibition aims to present the three projects carried out by the different artists with children in three hospitals : The AZ ZUB in Brussels, Armand-Trousseau in Paris and San Rafael in Madrid, together with a selection of personal works by each of the three artists. This exhibition, the final result of the project, will provide an opportunity for a wider European audience to understand the different phases of its implementation and to discover different facets of contemporary art.
biog., tent., prijzen, bibliog. p. 56-57
Engels & Frans & Nederlands & Spaans
'Art à l'Hôpital en Europe / Ziekenhuiskunst in Europa / Art in the Hospital in Europe, Brussel - Madrid - Paris, Salle d'exposition de la Comunidad de Madrid, du 6 au 13 juin 2001 ; Paris, Septembre 2001 ; Hötel de Ville Bruxelles, du 4 au 15 juillet 2001
boek
Keywords: Bailly, Virginie; Claeyé, Catherine; Arrojo de Lamo, Fran; Fernagu, Harald; Brussel; Madrid; Paris